ПЛАНКТОННЫЕ БЕСПОЗВОНОЧНЫЕ ЖИВОТНЫЕ ОЗЕРО САЙКУЛЬ - Туремуратова, Г.И.; Нагметов, Х.С. (SCIENCE and SOCIETY, 2023)
In this article, for the first time, the results of studies of planktonic invertebrates of Lake Saikul are presented. Zooplankton organisms of Lake Saikul from 2016 to 2020 Asplanchna priodonta, Keratella cochlearis, Kellicottia longispina, Alona rectangular, Daphnia longispina, Chydorus sphaericus, Arctodiaptomus salinus, Cyclops vicinus are represented, only A. priodonta K. cochlearis, D. longispina, C. sphaericus, C. vicinus were recorded in summer. It is briefly presented information on some investigated spicies.